Effect of Black Rice Bran ‘Sembada Hitam’ on T47D Breast Cancer Cells: Effect of Black rice bran on T47D - Cios Conara , Flafiani; Oktavya, Galuh; Asih Purwestri, Yekti; Nuriliani, Ardaning (Journal of Tropical Life Science, 2023)
Indonesians have a rich tradition of incorporating black rice into their diet as a functional food due to its high antioxidant content. This research investigates the effects of the ethanolic extract of